The Qur’anic Orientalis Discourse: An Analysis of H. A. R. Gibb’s Thought - Imam Muhajir Dwi Putra; Uun Yusufa; Ali Ridho (Universitas Islam Cordoba Banyuwangi, 2025)
This paper aims to explain the shift in Islamic studies in the West by describing H.A.R. Gibb's thoughts on the originality of the Qur'an. This study uses a descriptive-analytical method that can assist researchers in answering research questions. The research data sources consist of primary and secondary data. The primary data is Gibb's book entitled Mohammedanism, while the secondary data consists of scientific literature relevant to the research theme. The results of the study show that Gibb's approach to examining the originality of the Qur'an uses two approaches, namely: first, an Arabic grammatical approach that applies Eastern scholarship, which can be seen in Gibb's study of linguistic analysis and the context of the Qur'anic verses. Second, a historical approach, as the use of Western scholarship, can be seen in Gibb's description of the transmission and codification of revelation during the time of the Prophet Muhammad, the Khulafa Rasydun, and in the periods thereafter. These two approaches are important mechanisms in Gibb's study of the originality of the Qur'an.